种有机栽培基质的施肥方法及施肥装置 (2018)
本发明属于施肥技术领域，尤其涉及种有机栽培基质的施肥方法及施肥装置，所述施肥方法包括以下步骤：(1)干燥(2)粉碎(3)混悬(4)开沟(5)施肥(6)覆土(7)翻耕；所述施肥装置包括烘干装置、粉碎装置和浇肥装置。本发明提供的种有机栽培基质的施肥方法及施肥装置，其操作简单，成本较低，方便不溶于水的有机栽培基质的施肥，可大大降低施肥时的劳动强度，提高施肥效率和土壤对有机栽培基质的吸收率。 The invention belongs to the technical field of fertilization, and particularly relates to a fertilizing method and device for an organic culture medium. The fertilizing method includes the steps: (1) drying; (2) crushing; (3) suspending; (4) ditching; (5) fertilizing; (6) earth covering and (7) plowing. The fertilizing device comprises a drying unit, a crushing unit and a fertilizing unit. The fertilizing method and device for the organic cultivated medium have the advantages that the operation is simple, the cost is low, the fertilization for water-insoluble organic culture mediums is facilitated, the labor intensity during fertilization is greatly reduced, and the fertilizing efficiency and absorptivity of soil to the organic culture medium are improved.